2011
DOI: 10.2310/jim.0b013e31822467cd
|View full text |Cite
|
Sign up to set email alerts
|

APOA4 Polymorphism as a Risk Factor for Unfavorable Lipid Serum Profile and Depression: A Cross-Sectional Study

Abstract: Our data suggest that 360His allele might be a risk factor for depression and unfavorable lipid profile and depression for elderly people in the Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 41 publications
(67 reference statements)
0
7
0
Order By: Relevance
“… 16 APOA4 polymorphism has been reported as a risk factor for an unfavorable lipid serum profile. 17 On the other hand, a growing body of evidence suggests that obesity, hypertriglyceridemia, and reduced high-density lipoprotein cholesterol (HDL-c) is important in the development of cognitive impairment and AD. APOA1 was also observed at lower levels in AD patients via proteomic two-dimensional gel electrophoresis in 2006.…”
Section: Introductionmentioning
confidence: 99%
“… 16 APOA4 polymorphism has been reported as a risk factor for an unfavorable lipid serum profile. 17 On the other hand, a growing body of evidence suggests that obesity, hypertriglyceridemia, and reduced high-density lipoprotein cholesterol (HDL-c) is important in the development of cognitive impairment and AD. APOA1 was also observed at lower levels in AD patients via proteomic two-dimensional gel electrophoresis in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Small interfering RNA knockdown of Sort1 in the mouse was shown to alter plasma LDL, indicating that this is likely the causal gene in this gene cluster (Musunuru et al, 2010). ZNF259 is adjacent to APOA5, APOA4, APOC3, APOA1, and BUD13, all of which have been previously associated with differences in circulating plasma lipids (Pollin et al, 2008; Teslovich et al, 2010; Ota et al, 2011; Global Lipids Genetics Consortium, 2013; Aung et al, 2014). These genes are in high linkage disequilibrium, and although functional studies have demonstrated a clear role for apolipoprotein genes in regulating lipids (Ito et al, 1990; Rubin et al, 1991; Pennacchio & Rubin, 2003), additional studies are needed to fully understand how these genes influence disease.…”
Section: Discussionmentioning
confidence: 86%
“…33 Loss of appetite and thirst is one of the fundamental characteristics of chronic fatigue, and thus the differential expression of ApoA-IV represents a highly relevant finding. A polymorphism of the APOA4 gene is associated with depression, 34 and upregulation of APOA4 gene expression was significantly associated with poststroke depression. 35 In addition, in a recent plasma proteomic study of late-life depression, ApoA-IV protein was one of a panel of three proteins that could discriminate depressive from non-depressive elderly subjects.…”
Section: Discussionmentioning
confidence: 99%